EFEKTIVITAS KONSUMSI TABLET FE DITAMBAH JUS BAYAM HIJAU DAN MADU TERHADAP PENINGKATAN KADAR HB IBU HAMIL - Novi Wulan Sari; Sri Linda Afriana (Universitas Fort de Kock Bukittinggi, 2022)
One of the effects of malnutrition during pregnancy is anemia. Based on a preliminary research results, it can be seen that 7 from 10 of mothers were anemia. The purpose of this study is to determine the effectiveness of Fe tablet consumption with green spinach juiceand honey in increasing Hb level of pregnant mother.The type of this research was experimental research, pretest and posttestwith control group design. The research was conducted in Community Health Center of Rantau Panjang Merangin on May 2018. All pregnant women TM II-III who suffer from anemia were the population of this research. Then, they were 16 with purposive sampling technique. Data were analyzed univariate and bivariate with test T-Test Dependent. The mean result before Furthermore, the result of statistical test was seen that it is effective to consume the Fe tablet with green spinach juice and honey in increasing Hb level of pregnant mother with p value = 0,000.Then, there is difference of pregnant women Hb level in intervention group and control group p value = 0.012. In conclusion, there is affectivity of consumption Fe tablet with green spinach juice and honey to increase Hb Level of pregnant mother. It is expected that this research may help the pregnant women to find a solution to increase their Hb levels to avoid anemia.Keywords: Fe Tablet, Green Spinach and Honey, Anemia